Implementation of innovation policy based on the mechanism of public procurement - E. P. Malevich; E. A. Kirillova (Вестник университета, 2025)
At the present stage, implementation of national priorities for innovative, scientific and technical development, programmes for import substitution and ensuring technological sovereignty cannot be reached without participation of government agencies. A significant potential for speed growth and possibility of minimising costs in their implementation lies in the field of obtaining effects from integration of scientific research, industrial production, and government support. This determines the need to develop tools for using the available resources of the state of various kind to promote the creation of innovative goods, works, services and diffusion of such experience. The purposes of this study are to identify and disclose priority strategic directions, tools and resource opportunities for ensuring the implementation of modern innovative processes based on the analysis of world and Russian experience in this field as well as current changes in the production and economic entities themselves and environment of their interaction. According to the results of the conducted research, the most priority areas and support tools have been identified and described. There are also three levels of innovation in terms of importance, which should be considered within the framework of the mechanism of public procurement of goods, works, and services. This will allow us to base on changes in the participants of the innovation process and predict its transformation from the point of view of potential development as a system. The study complements the existing methodological tools and can be used to elaborate government programmes and measures to support innovation processes as well as in the framework of innovative development programmes for large domestic industrial enterprises with state participation.